2022
DOI: 10.1186/s12884-022-04470-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of three-dimensional MRI in the differentiation between angular pregnancy and interstitial pregnancy

Abstract: Background In clinical practice it is an ongoing challenge to distinguish between angular pregnancy and interstitial pregnancy. With the three-dimensional (3D) magnetic resonance imaging (MRI) being increasingly used, it is worth exploring its role in differentiating angular pregnancy from interstitial pregnancy. This study aims to investigate how 3D MRI can help reveal the differences between these two special pregnancies in the early diagnosis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, three-dimensional magnetic resonance imaging is considered to be of utmost help in differentiating interstitial ectopic pregnancy from angular pregnancy. In these cases, early diagnosis and avoidance of unnecessary interventions are crucial, contributing significantly to the prevention of hemorrhage and the reduction of morbidity and mortality [ 17 ]. Therefore, based on clinical findings, imaging results, and quantification of beta-chorionic gonadotropin hormone levels, the diagnosis of interstitial ectopic pregnancy can be established earlier and more accurately, providing the advantage of prompt treatment [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, three-dimensional magnetic resonance imaging is considered to be of utmost help in differentiating interstitial ectopic pregnancy from angular pregnancy. In these cases, early diagnosis and avoidance of unnecessary interventions are crucial, contributing significantly to the prevention of hemorrhage and the reduction of morbidity and mortality [ 17 ]. Therefore, based on clinical findings, imaging results, and quantification of beta-chorionic gonadotropin hormone levels, the diagnosis of interstitial ectopic pregnancy can be established earlier and more accurately, providing the advantage of prompt treatment [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…If ultrasound findings are ambiguous or inconclusive, many authors recommend using MRI or, very rarely, a CT scan for such cases [ 19 , 37 , 38 ]. 3-D MRI has brought innovation to the diagnosis and distinction between angular and interstitial ectopic pregnancies [39] .…”
Section: Discussionmentioning
confidence: 99%
“…An angular pregnancy implant is medial to the uterotubal junction, and it is possible to continue the pregnancy with careful observation [ 5 , 13 , 16 ]. In contrast, an interstitial pregnancy is implanted in the interstitial portion of the fallopian tube that lies in the uterine myometrium and has a high rate of maternal morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, a GS was observed in the uterine cavity, and the chorionic sac was near the lateral edge of the uterine cavity, surrounded by a thick myometrial layer (> 5 mm) [ 19 ]. Furthermore, Jansen et al [ 16 ] suggested the following clinicosurgical criteria to define an angular pregnancy: (1) clinical presentation with painful asymmetric enlargement of the uterus; (2) direct observation (i.e., surgical) of lateral uterine distention with lateral displacement of the round ligament; and (3) retention of the placenta in the uterine angle. In our case, asymmetric enlargement of the uterus and displacement of the round ligament laterally are observed.…”
Section: Discussionmentioning
confidence: 99%